Aplikasi Media Pembelajaran Stellarium untuk Meingkatkan Hasil Belajar Siswa pada Materi Tata Surya Kelas VI Sekolah Indonesia Davao, Filipina - Riski, Yunia Tiara; Huda, Muhammad Nur; Widodo, Wahono; Dayu, Dian Permatasari Kusuma (Universitas Pendidikan Indonesia, 2025)
This research aimed to improve learning outcomes on solar system material by applying Stellarium learning media. Students' low understanding of abstract concepts related to solar system material is the background for this research. Apart from that, being born and raised in the Philippines and coming from various regions in Mindanao means that Davao Indonesian School students have basic problems regarding understanding language and abstract things so that students do not understand the substance of the material being taught. The science study results found that 50% of grade VI students at the Indonesian School of Davao had not met minimum criteria of 70 in the Solar System material. The research was conducted in Grade VI, school year of 2022/2023. Research activities were carried out according to the classroom action research stages including planning, implementation, observation and reflection stages. The data in this research was processed using quantitative and qualitative analysis. The research results showed an increase in student learning outcomes in each cycle, with an average of 75 in cycle I (classical completeness 62.5%) and 80 in cycle II (classical completeness 87.5%). The conclusion of this research is that applying Stellarium technology in learning solar system material can improve the learning outcomes of class VI students at the Indonesian School in Davao, Philippines.